Were Mask, Distance, and Hygiene Measures Sufficient? A Field Study on Istanbul Municipalities in the Context of Human Rights Cities - Bayraktar, Erdal (Journal of Applied And Theoretical Social Sciences, 2023)
After the local administrators of Rosario in Argentina declared it a Human Rights City (HRC) in 1997, administrators of many other cities around the world also joined this movement. The HRC declaration entailed a commitment to leveraging local policies to localize universal human rights norms, while also establishing participatory mechanisms that include vulnerable groups. The capability approach provides a framework for evaluating the outcomes of these practices, as it focuses on the obstacles that prevent individuals from realizing their own potential. The objective of this article is to assess HRC practices during the Covid-19 pandemic in relation to individual freedoms and capabilities. Therefore, the practices of Maltepe and Zeytinburnu municipalities, which participated in the Turkey HRC Project, were compared with the practices of Büyükçekmece and Üsküdar municipalities in terms of the capabilities of their respective city residents. The study involved a sample of 5,022 people from these municipalities. The results revealed that residents of project-participant municipalities were statistically more likely to apply for municipal support (p=0.005), but there was no significant difference between municipalities with and without project participants regarding receiving municipal support, exposure to discrimination, awareness of municipal activities, and adequacy of activities.